A Compact High-Power Ultra-Wideband Bipolar Pulse Generator. (16th October 2021) - Wu, Zhaoyang; Lu, Wei; Ding, Enyan; Bao, Xiangyang; Yang, Zhoubing; Song, Falun
Abstract : A compact high-power ultra-wideband bipolar pulse generator based on a modified Marx circuit is designed, which is mainly composed of a primary power supply, Marx generator, sharpening and cutoff subnanosecond spark gap switches, and coaxial transmission lines. The Marx generator with modified circuit structure has thirty-two stages and is composed of eight disk-like modules. Each module consists of four capacitors, two spark gap switches, four charging inductors, and a mechanical support. To simplify the design of the charging structure and reduce the number of switches, four groups of inductors are used to charge the capacitors of the Marx generator, two of which are used for positive voltage charging and the other two for negative voltage charging. When the capacitor of each stage is charged to 35 kV, the maximum output peak voltage can reach 1 MV when the Marx generator is open circuit. The high-voltage pulse generated by the Marx generator charges the transmission line and forms a bipolar pulse through sharpening and cutoff switches. All transmission lines used for bipolar pulse generation have an impedance of 10 Ω. When the 950 kV pulse voltage generated by the Marx generator is fed into the transmission line, the bipolar pulse peak voltage can reach 390 kV, the center frequency of the pulse is about 400 MHz, and the output peak power is about 15.2 GW.